Experimental Investigation on the Perturbation Length for Air–Water Flow Upstream and Downstream of U-Bends - Ma, Xiaoxu; Liu, Taicheng; Dai, Nan; Tian, Maocheng; Li, Shijie (Frontiers in Energy Research, 2022)
In this work, the perturbation length of vertical U-bend effects on the air–water two-phase flow in their adjacent straight tubes was investigated experimentally at ambient pressure and temperature. The experimental database covered test sections with three inner diameters of U-tubes (9, 12, and 16 mm), two curvature ratios (8.33 and 12.5), and two orientations (downward and upward). The air and water superficial velocities varied from 0.18 to 25.11 m/s and from 0.11 to 1.98 m/s, respectively. The dissipation of U-bend effects in the regions upstream and downstream of U-bends is characterized by the variation regularities of segmental pressure gradients along the contiguous straight tubes. It was found that the significant value of the dimensionless perturbation length (Lp/D) is less than 60 for the experimental conditions in this study. The influences of the inlet volume void fraction, two-phase mixed Froude number, mixed Weber number, and mixed Dean number on dimensionless perturbation length (Lp/D) are similar. With the increase in these parameters, Lp/D presents a unimodal distribution which first increases and then decreases. The maximum value of Lp/D takes place at a volume void fraction of around 90%. New dimensionless correlations to predict the influence length of U-bends on the straight tubes upstream and downstream have been provided. The prediction errors of 80% of data are within ± 30% compared with the present experimental data.